Impact analysis of expanded access to ketamine for treatment-resistant depression - Thanh Lu; Sophia D’Angelo; Zohra Tayebali; Matthew Dempsey; Kristen Giombi; Olga Khavjou (Journal of Comparative Effectiveness Research)
Aim: This study aimed to estimate the economic impacts of expanded access to ketamine relative to electroconvulsive therapy (ECT) by offering intravenous ketamine to US patients with nonpsychotic treatment-resistant depression (TRD) and moderate-to-severe depression. Materials & methods: A population-level Markov simulation model with key parameters from a randomized trial was used to simulate the economic impacts of managing TRD with intravenous ketamine versus ECT over a 5-year horizon. Health states included response of depression in the acute treatment phase and continued treatment and relapse in the maintenance phase. The model estimated costs associated with healthcare utilization (direct costs) and time loss (indirect costs) from patient, caregiver, payer and societal perspectives. Model uncertainty was assessed with one-way sensitivity, probabilistic sensitivity and scenario analyses. Results: In year 1, our model included 350,000 eligible patients. In years 2 through 5, our model added 11,296 eligible patients annually. Expanded access to ketamine to manage TRD was projected to increase the number of patients receiving treatment by 75,000 patients in year 1 and 4292 patients annually in subsequent years. Over 5 years, expanded access to ketamine would result in a net positive societal savings of $828.2 million annually ($95.3 million to patients and $743.7 million to payers). However, expanded ketamine access would impose an additional $10.8 million burden on caregiver time annually. Conclusion: For US patients with TRD and moderate-to-severe depression, ketamine may be a noninferior treatment relative to ECT to improve depression symptoms. Expanded access to ketamine treatment would result in net savings to the patients, payers and society.